FGFR1: TACC1 fusion is a frequent event in molecularly defined extraventricular neurocytoma - Sievers, Philipp; Stichel, Damian; Schrimpf, Daniel; Sahm, Felix; Kölsche, Christian; Reuss, David; Wefers, Annika K.; Reinhardt, Annekathrin; Huang, Kristin; Ebrahimi, Azadeh; Hou, Yanghao; Pajtler, Kristian Wilfried; et al. (Acta neuropathologica, 2018)
Extraventricular neurocytoma (EVN) is a rare primary brain tumor occurring in brain parenchyma outside the ventricular system. Histopathological characteristics resemble those of central neurocytoma but exhibit a wider morphologic spectrum. Accurate diagnosis of these histologically heterogeneous tumors is often challenging because of the overlapping morphological features and the lack of defining molecular markers. Here, we explored the molecular landscape of 40 tumors diagnosed histologically as EVN by investigating copy number profiles and DNA methylation array data. DNA methylation profiles were compared with those of relevant differential diagnoses of EVN and with a broader spectrum of diverse brain tumor entities. Based on this, our tumor cohort segregated into different groups. While a large fraction (n = 22) formed a separate epigenetic group clearly distinct from established DNA methylation profiles of other entities, a subset (n = 14) of histologically diagnosed EVN grouped with clusters of other defined entities. Three cases formed a small group close to but separated from the epigenetically distinct EVN cases, and one sample clustered with non-neoplastic brain tissue. Four additional samples originally diagnosed otherwise were found to molecularly resemble EVN. Thus, our results highlight a distinct DNA methylation pattern for the majority of tumors diagnosed as EVN, but also indicate that approximately one third of morphological diagnoses of EVN epigenetically correspond to other brain tumor entities. Copy number analysis and confirmation through RNA sequencing revealed FGFR1-TACC1 fusion as a distinctive, recurrent feature within the EVN methylation group (60%), in addition to a small number of other FGFR rearrangements (13%). In conclusion, our data demonstrate a specific epigenetic signature of EVN suitable for characterization of these tumors as a molecularly distinct entity, and reveal a high frequency of potentially druggable FGFR pathway activation in this tumor group.